(untitled) (Journal of Information Technologies in Education (ITE), 2011)
The network «Partners in Learning Network» is presented in the article – the Ukrainian segment of global educational community. PILN is created with support of the Microsoft company for teachers who use information communication technology in their professional work. The PILN’s purpose and value for Ukrainian teachers, for their professional dialogue and collaboration are described in the article. Functions of PILN’s communities for teacher’s cooperation, the joint decision of questions and an exchange of ideas and of technique, teaching tools for increase of level of ICT introduction in educational process are described.